2013
DOI: 10.1063/1.4820003
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of the quantum rules for identical particles

Abstract: Ensemble fluctuations and the origin of quantum probabilistic rule Some general commutation rules and identities for three-dimensional quantum-mechanical operators Am.Abstract. We present a proof of the Symmetrization Postulate for the special case of noninteracting, identical particles. The proof is given in the context of the Feynman formalism of Quantum Mechanics, and builds upon the work of Goyal, Knuth and Skilling [1], which shows how to derive Feynman's rules from operational assumptions concerning expe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…The basic idea of approaching identical particles from Refs. [1,2] completely sidesteps any criticism of the legitimacy of using particle labels, and does not result in a curved configuration space. Instead, it assumes that a certain problem has been solved for distinguishable particles, that is, with particle labels, and sees what consistent ways there are to combine these solutions into a solution to the identified system.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The basic idea of approaching identical particles from Refs. [1,2] completely sidesteps any criticism of the legitimacy of using particle labels, and does not result in a curved configuration space. Instead, it assumes that a certain problem has been solved for distinguishable particles, that is, with particle labels, and sees what consistent ways there are to combine these solutions into a solution to the identified system.…”
Section: Discussionmentioning
confidence: 99%
“…The research reported in Neori and Goyal [2] and Goyal [1] was able to overcome the dependence on analyticity. Additionally, one of the implicit assumptions in Ref.…”
Section: Behavior Of Identical Particles In Quantum Mechanicsmentioning
confidence: 93%
See 3 more Smart Citations